Effect of the Alcoholic Extract of Myrtus communis in Healing and curing the infected wounds by Staphylococcus aureus in white mice for specific Time Periods - Abedurazzaq Mahmoud; Enam Abdulmoum (College of Education for Pure Sciences, 2008)
Abstract The study involved the isolation and characterization of some species of bacteria caused the wound infections. A number of (180) pus samples were collected from patients suffering from infected wounds. The Staphylococcus aureus were isolated and characterized in (29%) percentage according to the other bacterial species. The alcoholic extract of Myrtus communis under studying the inhibitory effect in the isolations bacteria, this extract showed high inhibitory effect on the isolated bacteria from the infected wounds and Staph. aureus was the most susceptible bacteria species against this extract. The (MIC) for the tested bacteria was determined and the results showed that the (MIC) for the alcoholic extract of the fruit of Myrtus communis was (0.25) mg/cm3. According to the results, the alcoholic extract of the fruit of Myrtus communis was selected to test its activity In vivo, so the extract showed a good effect in healing and curing the infected experimental wounds by the Staph. aureus in white mice strain BALB/c in a period of less than ten days, as it is clear in pictures of this study.